2019
DOI: 10.1159/000496195
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Retinal and Choroidal Changes in Retinal Vein Occlusion Analyzed by Two Different Optical Coherence Tomography Angiography Devices

Abstract: Purpose: To investigate retinal and choroidal microvascular changes and structural choroidal involvement in retinal vein occlusion (RVO). Methods: Retrospective analysis of treatment-naïve macular edema secondary to RVO, studied by optical coherence tomography (OCT) and OCT angiography (OCTA), before and after the loading phase of intravitreal injections of ranibizumab (IVR-LP). OCTA was performed using two different devices: AngioVue RTVue XR Avanti (spectral-domain OCTA) and Zeiss PLEX® Elite 9000 (swept-sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Andrew Winegarner et al [34] found no significant changes in mean VD 12 months after anti-VEGF injections in patients with RVO, although higher VD and a smaller FAZ were associated with better BCVA. Other authors [24,35,36] confirmed no significant variation of macular VD after treatment.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Andrew Winegarner et al [34] found no significant changes in mean VD 12 months after anti-VEGF injections in patients with RVO, although higher VD and a smaller FAZ were associated with better BCVA. Other authors [24,35,36] confirmed no significant variation of macular VD after treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies [34,35] focused on vessel density changes and macular perfusion in RVO after anti-VEGF using OCTA technology. Andrew Winegarner et al [34] found no significant changes in mean VD 12 months after anti-VEGF injections in patients with RVO, although higher VD and a smaller FAZ were associated with better BCVA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations